2017
DOI: 10.1159/000475813
|View full text |Cite
|
Sign up to set email alerts
|

Skin Perfusion Changes within 12 h after Axillary Plexus Block

Abstract: Background/Purpose: An improvement of the blood flow would be beneficial in microvascular upper-extremity reconstruction and in digit replantation. In the present work, skin perfusion changes and their duration due to axillary plexus block were quantified. Methods: The peripheral blood flow of the upper extremities in 20 patients undergoing trapeziectomy under axillary plexus block was analyzed. Results: Laser Doppler spectrophotometry was used to measure perfusion factors over a 12-h period, with the contrala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Our results are in line with previous work from Wenger et al, who conducted a prospective analysis of the effects of regional anesthesia on cutaneous microcirculation [ 5 , 6 ]. Whereas their investigation focused on the quantification and course of the elicited effects, our goal was to analyze acute effects within different tissue layers and, therefore, different vascular territories.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with previous work from Wenger et al, who conducted a prospective analysis of the effects of regional anesthesia on cutaneous microcirculation [ 5 , 6 ]. Whereas their investigation focused on the quantification and course of the elicited effects, our goal was to analyze acute effects within different tissue layers and, therefore, different vascular territories.…”
Section: Discussionsupporting
confidence: 93%
“…The German Speaking Society for Microsurgery of Peripheral Nerves and Vessels recommends the utilization of regional anesthesia techniques in the context of microsurgical reconstructive procedures according to an expert opinion-based consensus statement [ 2 , 3 ]. Derived from the available literature, it is commonly accepted that regional anesthesia has a beneficial influence on perfusion dynamics as well as on local microcirculation [ 4 , 5 , 6 ]. However, despite earlier publications already acknowledging the benefits of regional anesthesia in the context of microsurgical interventions, such as digital replantation, there is only limited evidence available from clinical trials with an emphasis on its effects on free flap perfusion and specifically, microcirculatory characteristics [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdelnasser et al [13] reported that PI may be useful in determining the success of a supraclavicular blockade in patients undergoing orthopedic surgery. Wenger A et al [16] suggested that a brachial plexus blockade should be used especially where perfusion is important, in that the increase in skin perfusion remains for 6-12 hours after the brachial plexus blockade. In a study by Han-Hsiang Su et al [2], a continuous brachial plexus blockade was found to be effective in maintaining the continuity of grafts after a microsurgical implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathicolytic effects produced by pain catheters coupled with limb analgesia to increase tissue perfusion have been previously described. 6 The delicate nature of microvascular anastomoses requires meticulous control of pain and sympathetic physiology, though to date, the role of perineural infusion in the lower extremity free flap has been undefined. PACU flap management revolves around achieving normothermia, stable or even increased cardiac output, and adequate urine output to maximize perfusion.…”
Section: Discussionmentioning
confidence: 99%